A comparative study on the role of public-private partnerships and green investment banks in boosting low-carbon investments - Dharish David; Anbumozhi Venkatachalam (Asian Development Bank Institute (ADBI), 2018)
Following the successful climate agreement in Paris, global attention shifted quickly to how countries will achieve their nationally determined contributions. To achieve the goals, governments need to make full use of the private sector capacity to unlock much larger flows of private investment in low-carbon green infrastructure. This paper focuses on two different types of mechanism, public-private partnerships (PPPs) and green investment banks (GIBs). PPPs are more practical for countries that have robust demand, and are complemented by strong institutions and governance, protection of investments, and dispute resolution mechanisms. In contrast, the other options for green investments should use innovative transactions, risk-reduction structures, and market expertise. Although their common objective is to upscale low-carbon investment, both PPPs and GIBs have been established in a variety of national contexts to achieve a range of goals, including access to concessional capital at lower interest rates and longer tenures for green investments. This paper examines the rationale, mandates, and financing activities of these two categories of financial architecture within the context of India and Japan. It provides stocktaking of the actual and potential use of these two approaches, and for strengthening bilateral cooperation between India and Japan.
Keywords: F21; F34; G29; Q28; 330; climate change; clean energy; green infrastructure; green investment bank; public-private partnership